2013
DOI: 10.1158/1538-7445.am2013-5462
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5462: MEDI3185, a potent anti-CXCR4 antibody, inhibits tumor cell migration, signaling and tumor growth in preclinical models.

Abstract: The chemokine receptor CXCR4 is a seven-transmembrane G-protein coupled receptor that mediates chemotaxis and cell migration upon stimulation via its ligand, stromal-derived factor 1 (SDF-1), also called CXCL12. CXCR4 is normally expressed on bone marrow stem and progenitor cells, various circulating lymphocytes, endothelial precursor cells, tissue macrophages and fibroblasts but the aberrant overexpression of CXCR4 is linked to various hematological malignancies, solid tumors and metastatic neoplasms. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Overexpression is associated with a range of malignancies including acute myelogenous leukemia, 15 pancreatic cancer, breast cancer, 16 colorectal cancer, 17 melanoma, 18 neuroblastoma, 19 renal cell carcinoma, 20 and prostate cancer. The CXCR4, which is also called fusin or cluster of differentiation 184, is normally expressed in bone marrow and progenitor cells, lymphocytes, endothelial precursor cells, tissue macrophages, and fibroblasts.…”
Section: Cxcr4 C-x-c Chemokine Receptor Type 7 and Their Ligands Inmentioning
confidence: 99%
“…Overexpression is associated with a range of malignancies including acute myelogenous leukemia, 15 pancreatic cancer, breast cancer, 16 colorectal cancer, 17 melanoma, 18 neuroblastoma, 19 renal cell carcinoma, 20 and prostate cancer. The CXCR4, which is also called fusin or cluster of differentiation 184, is normally expressed in bone marrow and progenitor cells, lymphocytes, endothelial precursor cells, tissue macrophages, and fibroblasts.…”
Section: Cxcr4 C-x-c Chemokine Receptor Type 7 and Their Ligands Inmentioning
confidence: 99%
“… 20 We have also reported a fully human antagonistic anti-CXCR4 mAb, MEDI3185 (IgG1, κ). 21 MEDI3185 can inhibit tumor growth in hematologic tumors as a single-agent and shows combination activity in ovarian tumor models. While interest in developing anti-CXCR4 mAb therapy increases, so does understanding the molecular basis for the corresponding mechanism(s) of action.…”
Section: Introductionmentioning
confidence: 99%
“…In a phase I study in healthy volunteers (NCT01374503), ALX-0651 demonstrated appreciable CXCR4 targeting ability; however, the study and any subsequent investigations into ALX-0651 as an anti-cancer agent were halted due to an inability to outcompete other CXCR4 antibodies [209]. Other anti-CXCR4 antibodies include LY2624587, hz515H7 (F-50067), and MEDI3185, which exhibit anti-tumor activity in hematological malignancies in mice [210][211][212]. LY2624587 (NCT01139788) and hz515H7 have both been tested in Phase I clinical trials.…”
Section: Antibodiesmentioning
confidence: 99%